The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1381/0960892042583897
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessed Emotional Factors Contributing to Increased Weight Gain in Pre-surgical Bariatric Patients

Abstract: To increase the likelihood of long-term maintenance of weight loss, a significant portion of this patient population would benefit from interventions targeting overcoming boredom, reducing stress, and managing depression. In the pre-surgical evaluation, it is important to identify those patients who are "emotional eaters" and to refer them for appropriate interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 5 publications
2
38
0
1
Order By: Relevance
“…23 There is also a wide consensus about the association between weight cycling and binge eating. 5,24,25 On the contrary, an association between weight cycling and depression in obesity in general has been reported in a few cohorts, 20,26,27 but denied in other settings. 28,29 There is no unequivocal definition for weight cycling.…”
Section: Discussionmentioning
confidence: 99%
“…23 There is also a wide consensus about the association between weight cycling and binge eating. 5,24,25 On the contrary, an association between weight cycling and depression in obesity in general has been reported in a few cohorts, 20,26,27 but denied in other settings. 28,29 There is no unequivocal definition for weight cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Eating in response to negative emotional states and continuing to eat despite feeling full are forms of nonhungry eating related to higher reports of hunger and poorer weight outcomes. Others have observed eating in response to emotions among bariatric patients [12,29] and, in nonsurgical populations, an increased propensity for fatty and sweet foods [30,31]. It has been suggested that "emotional eaters" have difficulty articulating negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Poorer 12-month weight outcomes have, however, been associated with greater subjective hunger and dietary disinhibition [10]. High levels of depression [11] and eating in response to emotional cues [12] are also found among bariatric surgery candidates. Although preoperative depression has not predicted poorer weight loss at 1 year [3], the association between postsurgical mood, eating behavior, and weight outcome is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies indicate that that poorer weight loss is associated with difficulties complying with post operative eating guidelines (Rusch & Andris 2007) and research indicates that individuals continue to have 'maladaptive and psychologically distressing eating behaviour' post WLS (Niego et al, p356, 2007). Similarly, Walfish (2004) concluded that 40% of individuals seeking WLS would identify themselves as 'emotional eaters ' and Saunders (2004) reported that for some people difficulties adjusting to the restrictions of surgery left individuals more likely to over eat post surgery and to show 'grazing' behaviour. In contrast, however, Rusch and Andris (2007) suggested that emotional eating is reduced post WLS as eating high-fat food leads to the negative consequence of nausea or vomiting and Fischer et al (2007) found that emotional eating was not predictive of surgical outcome at 8 months.…”
Section: Introductionmentioning
confidence: 99%